Assessment of phenolic and flavonoid contents, antioxidant and antimicrobial activities of Moroccan propolis - Abdelghani Aboukhalaf; Jalali Abdessadek; Youssef Lahlou; Nadia Ikhiar; Seloua Essaih; Jamila Elbiyad; Adil Kalili; Belkassem El-Amraoui; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2024)
Background. Despite the extensive literature focused on propolis extract, few data exists on the bioactive compounds and biological activities in the Moroccan propolis and its economic value is low. Objective. In this research, the aim was to evaluate the total content of phenols and flavonoids as well as the antioxidant, antibacterial and antifungal activities of Moroccan propolis. Material and Methods. The polyphenol and flavonoid content of the Moroccan propolis from three geographic regions, was quantified in the ethanolic extract by colorimetric methods using folin-ciocalteu and aluminum chloride. The antioxidant activity was evaluated by the DPPH test and expressed as IC50. Disk diffusion and broth microdilution methods were used to examine in vitro antimicrobial activity against known human microorganism pathogens. Results. The obtained data revealed that Moroccan propolis samples presented significant variations in total polyphenols and flavonoids. All samples showed significant antioxidant activity with IC50 values ranging from 4.23±0.5 to 154±0.21 μg/ mL. A strong correlation between total phenolic activity, flavonoids and antioxidant activity was found. The in vitro study of antibacterial activity showed that the propolis samples exhibited a range of growth inhibitory actions against all bacterial strains tested with the highest activity against gram-positive bacteria. Only propolis from the Sidi Bennour region demonstrated an antifungal activity. Conclusion. The study data show that Moroccan propolis extracts have a promising content of antioxidant and antimicrobial compounds that could be exploited to prevent certain diseases linked to oxidative stress and pathogenic infections.